THE TYPES OF CORPORA: GENERAL , SPECIALIZED AND PARALLEL - Abdullayeva Nasiba O’ktamovna; Abdullajonova Hakima (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: This paper explores three major types of corpora widely used in modern linguistic research: general corpora, specialized corpora, and parallel corpora. It provides a comprehensive overview of their characteristics, design principles, applications, and advantages within fields such as lexicography, computational linguistics, translation studies, discourse analysis, and language pedagogy. The study highlights how each corpus type contributes uniquely to linguistic inquiry while also demonstrating their complementary roles in empirical language analysis. Through comparing these corpora and examining notable examples, the paper emphasizes the importance of corpus-driven and corpus-based approaches in understanding language patterns and supporting technological innovations in the era of big data.